Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00104-007-1368-7
|View full text |Cite
|
Sign up to set email alerts
|

N.-phrenicus-Stimulation bei biventrikulären Schrittmachern

Abstract: Approach in case of PNS: 1. push or pull the lead within the same vein, 2. change to a different vein, 3. maintain position in case of a safe distance between the phrenic nerve and the pacing threshold, 4. change the lead type to achieve stable anchorage at adequate positions, 5. use a device featuring electronic repositioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, selecting a CRT device featuring cathode programmability should be the first step in implantation to minimize the risk of PS, whereas lead repositioning should be performed as the last resort. 18 We observed that PS evaluation at implantation is not 100% predictive, owing to the body position (detected only after implantation in 27 patients), a fact that reinforces the need for cathode programmability. Automatic verification of capture helped to manage 4 patients who had a difference in PS-LV threshold of Յ2 V and may be considered as complementary to cathode programmability in this instance.…”
Section: Response To Crt and Ps Managementmentioning
confidence: 69%
“…Thus, selecting a CRT device featuring cathode programmability should be the first step in implantation to minimize the risk of PS, whereas lead repositioning should be performed as the last resort. 18 We observed that PS evaluation at implantation is not 100% predictive, owing to the body position (detected only after implantation in 27 patients), a fact that reinforces the need for cathode programmability. Automatic verification of capture helped to manage 4 patients who had a difference in PS-LV threshold of Յ2 V and may be considered as complementary to cathode programmability in this instance.…”
Section: Response To Crt and Ps Managementmentioning
confidence: 69%
“…PNS is found in 13%-18% of CRT implantations, and it is one of the main reasons for intraoperative lead repositioning from an anatomically acceptable location. 18,19 Pacing with high energy during implantation may help to avoid subsequent PNS, but despite high-energy stimulation, intraoperative testing in a supine position cannot rule out later PNS in other body positions, 20 even if the electrode remains in the same place. In seven cases, a new, minimally invasive method was performed using an ablation catheter for repositioning of the lead via a femoral approach.…”
Section: Discussionmentioning
confidence: 99%